2012
DOI: 10.1074/jbc.m111.304857
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Sphingomyelinase 2 Deficiency Increases Hyaluronan Synthesis by Up-regulation of Hyaluronan Synthase 2 through Decreased Ceramide Production and Activation of Akt

Abstract: Background:Fibroblasts from the fro/fro mouse contained reduced amounts of ceramides and elevated amounts of hyaluronan (HA). Results: Increased HA secretion was associated with increased activity of the Akt pathway and enhanced expression of the HAS2 gene. Conclusion: HA synthesis is regulated by NSMase2/ceramide through ceramide-activated phosphatase PP2A and Akt signaling pathway. Significance: There is a direct link between sphingolipid and glycosaminoglycan metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 59 publications
6
61
0
Order By: Relevance
“…Ceramides have been shown to reduce the level of Akt phosphorylation by activating protein phosphatase 2A (PP2A) (58). The phosphorylation level of PP2A in fro/fro fibroblasts is reduced (50). Taken together, in the maturing phase of chondrogenesis, BMP-2-induced nSMase2 is thought to release ceramide, which in turn activates PP2A to inactivate Akt and the subsequent chondrogenic molecular cascades (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceramides have been shown to reduce the level of Akt phosphorylation by activating protein phosphatase 2A (PP2A) (58). The phosphorylation level of PP2A in fro/fro fibroblasts is reduced (50). Taken together, in the maturing phase of chondrogenesis, BMP-2-induced nSMase2 is thought to release ceramide, which in turn activates PP2A to inactivate Akt and the subsequent chondrogenic molecular cascades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a significant level of Has2 expression and hyaluronan synthesis in fro/ fro fibroblasts and that nSMase2 suppressed production of Has2 via inactivation of Akt (50). Taken together, if Smpd3/ nSMase2 also regulates expression of Has2 in chondrocytes, Has2 might be another target for the inhibitory action of Smpd3/nSMase2 on chondrocyte hypertrophic maturation.…”
Section: Gw4869 or C 2 -Ceramide Promotes Or Eliminates Respectivelymentioning
confidence: 96%
See 1 more Smart Citation
“…Ionizing radiation activates acid sphingomyelinase to produce ceramide which promotes the induction of apoptosis (Haimovitz-Friedman et al 1994), implicating a crucial role for this enzyme in mediating stress-induced apoptosis (Santana et al 1996). Conversely, a cell permeable and non-competitive inhibitor of neutral sphingomyelinase (GW4869) blocks ceramide synthesis to rescue cell death in numerous cell types, such as cochlear hair cells (Chi et al 2014), retinal pigment epithelial cells (Kucuksayan et al 2014) and fibroblasts (Qin et al 2012). At least four isoforms of neutral sphingomyelinase are expressed in mammalian cells, each with distinct biochemical properties, localizations and physiological roles [for a review, see (Airola and Hannun 2013)].…”
Section: Sphingolipid Metabolismmentioning
confidence: 99%
“…Furthermore, PI3K/Akt activation is associated with increased hyaluronan synthesis via a mechanism that involves S1P stimulation ( Fig. 5D) (Qin et al 2012). …”
Section: Heart Development and Ecm Remodelingmentioning
confidence: 97%